Witchcraft in Russia and Ukraine, 1000-1900 : a sourcebook - Kivelson, Valerie A. (Valerie Ann); Worobec, Christine D., 1955- (Ithaca [New York] : Northern Illinois University Press, an imprint of Cornell University Press, 2020)
"This book provides the first systematic overview of witchcraft laws and trials in Russia and Ukraine, combining scholarly commentary with primary source materials translated from Polish, Russian, and Ukrainian, most of which have never before been published" --
Historical Evolution, Law, and Prosecution -- Witchcraft and Politics in Muscovy and the Hetmanate -- Laws and Guidelines Concerning the Prosecution of Witchcraft, Late Twelfth Century to -- Witchcraft Trials' Processes (Charges and Counter-Charges) and Extra-Legal Prosecution of Witchcraft: Complete Records -- Healing and Harming -- Sex/Love/Anti-Love Magic -- Power Relations and Hierarchy -- Possession -- Satanic Pacts/Diabolism -- Orality/Literacy -- Specialists in Magic.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 26, 2020).
JSTOR
Keywords: Witchcraft -- Russia -- History; Witchcraft -- Ukraine -- History; Magic -- Russia -- History; Magic -- Ukraine -- History; Witchcraft -- Law and legislation -- Russia; Witchcraft -- Law and legislation -- Ukraine; Sorcellerie -- Russie -- Histoire; Sorcellerie -- Ukraine -- Histoire; HISTORY / Russia & the Former Soviet Union; Magic; Witchcraft; Witchcraft -- Law and legislation; Russia; Ukraine; witchcraft, magic, trials, laws, possession, Social Conditions, polish translation; Electronic books; History